Physiological responses during treadmill walking at a self-selected pace: comparison between genders - Ricardo W. Coelho; Bruno Santos; Cosme Franklim Buzzachera; Heriberto Colombo; Hassan Mohamed Elsangedy; Sergio Gregorio Da Silva; Kleverton Krinski; Wagner De Campos; Carlo Baldari (Universidade Federal de Santa Catarina, 2009)
The objective of this study was to compare % O2Max, %HRMax, %HRR, % O2R, and MET between genders during walking at a self-selected pace and to determine whether the self-selected pace was physiologically effective in maintaining and improving cardiorespiratory fitness. Seventeen men (age: 24.05 ± 3.3 years) and 17 women (age > 22.58 ± 2.67 years) were submitted to two experimental sessions: (I) anthropometric assessment and incremental exhaustion test, and (II) 20-min treadmill walking bouts at a self-selected pace. The independent Student t-test was used to determine differences between genders, at an alpha level of 0.05. No significant differences in %HRMax (58.38 ± 8.86 for men and 62.12 ± 5.91 for women), % O2Max (37.54 ± 10.75 for men and 40.34 ± 7.27 for women), %HRR (36.83 ± 11.77 for men and 38.46 ± 8.33 for women), or % O2R (31.88 ± 11.17 for men and 34.70 ± 7.74 for women) were observed between genders. However, the walking speed selected (km.h-1) was higher in men (5.96 ± 0.66, p < 0.001) than women, a finding that probably resulted in higher MET values for men (6.07 ± 1.57, p < 0.05) compared to women (5.23 ± 0.77). In conclusion, both genders selected a walking pace that was not effective in maintaining or improving cardiorespiratory fitness, but MET values were within the range indicated for the maintenance and reduction of body weight. The differences in METs observed between genders might be due to differences in walking speed and anthropometric characteristics.